A1_6 The Planet Phaeton - Mcculloch, Ariella; Carr, Natasha; Harrison, Joseph; Whitaker, Joshua (Physics Special Topics, 2022)
Whilst the main theory of the asteroid belt’s origin is left over remnants from when the protoplan- etary disc formed our Solar System, on theory is a destroyed planet: Phaeton. This paper aims to explore the characteristics of such a planet forming from the asteroids in the main belt. It is found to have a density of 2188.8 kg/m3, a radius of 6.4 × 105 m, orbital period of 1620.2 days, and an eccentricity of 0.2.